Solid Tumors and Factor VIII Antibodies - Hauser, Irene; Lechner, Klaus (Thrombosis and Haemostasis, 1999)
Purpose: To analyze the association between solid tumors and the occurrence of factor VIII antibodies and the response to treatment.Patients and Methods: Published case reports describing the association of a solid tumor and a factor VIII antibody retrieved from 20 data bases. 40 cases were reported and 27 cases were analyzable.Results: Factor VIII antibodies occurred in a close temporal relationship with the detection of the tumor in most cases. No association with a specific type of tumor could be identified. Immune suppressive treatment with prednisone ± cyclophosphamide was successful in the majority of cases.Conclusion: It is likely that there is a causal association between some solid tumors and factor VIII antibodies, but it is an extremely rare complication of cancer. The immunoglobuline nature of the inhibitor and the good response to immune suppressive treatment suggests that it is an autoimmune phenomenon. The pathogenesis is unknown.